De verzameling Het domein : version 2.0. (Sittard : Museum Het Domein Sittard, 2001)
Abramovic, Marina & Ulay ; Ackermann, Rita ; Aladogan, Eylem ; Alves, Maria Thereza ; Durham, Jimmie ; Andriesse, Paul ; D’Armagnac, Ben ; Beerens, Rudy ; Ben Ali, Rachid ; Besems, Korrie ; Biava, Laura ; Blok, Diana ; Blokland, Sara ; Botman, Harm ; Broucke, Koen ; De Bruyckere, Berlinde ; Clinckx, Christine ; Corbijn, Anton ; Dekkers, Ger ; Delvoye, Wim ; Diamond, Jessica ; Amie Dicke ; Dieteren, Jacques ; Dijkstra, Rineke ; Dolron, Désirée ; Drummen, Suzan ; Dumas, Marlene ; Durham, Jimmie ; Eberson, Henk ; Fahlström, Öyvind ; Fiddelers, Norbert ; Finke, Romy ; de Gaar, Leonne van ; Gaba, Meschac ; Gonzales, Mark ; Gordon, Kim ; Gudmundsson, Sigurdur ; de Haas, Deborah ; de Haas, Raph ; Hamelink, Eric ; Hazekamp, Risk ; Hermans, Benoît ; Hocks, Teun ; van Houwelingen, Hans ; Huisman, Michel ; Hyber, Fabrice ; Jaar, Alfredo ; Kinoshita, Suchan ; Knippenbergh, Mathieu ; Koelewijn, Job ; Kraijer, Juul ; Kruip, Germaine ; Lambermont, Robert ; Lamers, Ine ; van Lamsweerde, Inez ; Lemmen, Hans ; Lemmens, Nieke ; Lenders, Maurice ; Lester, Gabriël ; Lipski, Edward ; Mafille, Emmanuelle ; Manders, Mark ; Melgaard, Bjarne ; Merkoulov, Dmitri ; Mik, Aernout ; Mistiaen, Carlo ; Nollen, Arno ; de Nooijer, Paul ; Noorda, Ruchama ; Noordenbos, Corinne ; Olaf, Erwin ; Olde Wölbers, Saskia ; Oorebeek, Willem ; Panamarenko ; Pelletey, Dominique ; Penck ; Peper, Sanne ; Post, Liza May ; Preesman, Avery ; Prins, Lieve ; Rekula, Heli ; van Riessen, Wouter ; Rist, Pipilotti ; Samsom, Laura ; Schouten, Lydia ; Schwontkowski, Norbert ; Serse ; Sixma, Tjarda ; Smulders, Margriet ; Speakman, William ; Stern, Grete ; Tahon, Johan ; Tajiri, Shinkichi ; Tan, Fiona ; Tanaka, Iichiro ; Tee, Jennifer ; Templeton, Ed ; Ulay ; de Ven, Lidwien van ; Ventura, Julia ; Villevoye, Roy ; etc.
Speciale kast : CD-Rom
boek